Pembaharuan Peta Administrasi dan Peta Sarana Prasarana Desa Polenga Jaya Kecamatan Poli Polia Kabupaten Kolaka Timur - Haydir H (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The Community Service Program (KKN) in Polenga Jaya Village, Poli Polia District, focused on mapping the administrative area and identifying village facilities and infrastructure. The administrative map was designed to clearly and systematically document village boundaries, while the infrastructure map was designed to identify the location of public facilities that support the community's social, economic, educational, and religious activities. Data was obtained through field surveys, interviews with village officials, and spatial data processing using a Geographic Information System (GIS). These activities resulted in an informative and accurate map, which is expected to serve as a basis for village development planning and facilitate decision-making at the village government level.